A contradição das classes sociais presente no ensino superior: considerações sobre assistência estudantil - Durat, Kleber Rodrigo (2015)
As far as the capitalist bourgeois State is concerned, it is possible to affirm that the so-called capitalist System has been targeting actions aiming the constant pursuit for profit, which enters all aspects of social life of the working class. Social policies are the locus of attention of the government, considering the fact that its actions result from conflict and ideological disruption between the bourgeoisie and the proletariat. From such a perspective, the appropriation of social policies with profitable ends, by the government, impairs the unequal logic presented by the capitalist society. It is, thus, from that point of interests that the bourgeoisie drives the society ideology seeking the generation of profit and the maintenance of the capitalist system. Educational policies, mainly those concerning higher education, are the field where leading changes over the formation of educational parameters are taking place, making education increasingly fit for the working market interests in opposition to a formation concerned with the life and preparation of human beings. Actions in the Brazilian social policies scenario are alike. A minimum population benefits from programs, usually the most vulnerable portion in poverty conditions or the people who might give Capital profit in return. One of Brazilian s Government strategies to attend the market demands for qualified work force is the massive insertion of the working class into the higher education. Through programs such as the National Program of Student Assistance (PNAES), government has sought to assure that students in major socioeconomic vulnerability situation achieve to finish undergraduate programs in Federal Higher Education Institutions (IFES) by means of transferring financial resources and investing in interdisciplinary actions within Universities. The present work aims thus to analyze PNAES student assistance actions within the Federal University of Technology Paraná (UTFPR) through Scholarship Programs and their impact in diminishing academic evasion at UTFPR Francisco Beltrão Campus. By means of bibliographical and documental research in law-papers, decrees, institutional documents, and mainly students application forms and data form UTFPR s informational system we were able to lay information systematically in order to analyze them in three distinct but inseparable moments, which resulted in the three chapter of this work. The first chapter presents the creation of social policies and the relation between the bourgeois State and actions performed in the production and reproduction of the working class life. The second chapter aims to present the sequence to the understanding of the bourgeoisie intentions to conduce social ideology mainly that which concerns educational policies. As we comprehend the ways of education, the third chapter presents the analysis of UTFPR s student assistance in order to evaluate if actions taken from 2008 to 2012 effectively contributed to the permanence of students in the institution and to the decreasing of evasion from Francisco Beltrão Campus as well.